Suppressive effect of Rho-kinase inhibitors Y-27632 and fasudil on spike-and-wave discharges in genetic absence epilepsy rats from Strasbourg (GAERS) - ONAT, FİLİZ; KARAMAHMUTOĞLU, TUĞBA (SPRINGER, 2018)
Rho/Rho-kinase (ROCK) signaling contributes to neuroinflammation, epileptogenesis, and seizures in convulsive-type epilepsies. However, this pathway has not been investigated in absence epilepsy. We investigated RhoA activity in genetic absence epilepsy rats from Strasburg (GAERS) and the effects of ROCK inhibitors Y-27632 and fasudil on spike-and-wave discharges (SWDs) of GAERS. ROCK level and activity were measured by Western blot analysis in the brain areas involved in absence seizures (i.e., cortex and thalamus) and hippocampus. Male GAERS were stereotaxically implanted with bilateral cortical electrodes for electroencephalogram (EEG) recordings and/or guide cannula into the right ventricle. ROCK inhibitors were administered by intraperitoneal injection (1-10mg/kg for Y-27632 or fasudil) or intracerebroventricular injection (7-20nmol/5l for Y-27632 or 10-100nmol/5l for fasudil). EEG was recorded under freely moving conditions. Compared with Wistar rats, GAERS exhibited increased RhoA activity in the somatosensory cortex but not in the thalamus or hippocampus. The single systemic administration of Y-27632 and fasudil partially suppressed the duration and frequency of absence seizure, respectively. However, local brain administration caused a widespread suppressive effect on the total seizure duration, number of seizures, and the average individual seizure length. In summary, Rho/ROCK signaling may be involved in the pathophysiology of absence epilepsy. Furthermore, ROCK inhibitors can control the expression of absence seizure in GAERS, thus indicating that Y-27632 and fasudil have the potential to be used as novel anti-absence drugs.
Keywords: Absence epilepsy; Fasudil; GAERS; Rho; Rho-kinase; Y-27632; KAPPA-B INHIBITION; ROCK INHIBITOR; IN-VITRO; SOMATOSENSORY CORTEX; NETWORK MECHANISMS; CORTICAL-NEURONS; MODEL; SEIZURES; PROTECTS; INJURY